Hepatoprotective Activity of Stem Heart Wood of Spondias pinnata - GANGA RAO, B.; JAYA RAJU, N. (Asian Journal of Chemistry, 2010)
Spondias pinnata (Anacardiaceae) stem heart wood was prepared and tested for its hepatoprotective effect against carbon tetrachloride induced in rats. Alteration in the levels of biochemical markers of hepatic damage like SGPT, SGOT, ALP, bilirubin were tested in both treated and untreated groups. Carbon tetrachloride has enhanced the SGPT, SGOT, ALP and bilirubin levels. Treatment with ethyl acetate extract of S. pinnata stem heart wood (100, 200 and 400 mg/kg) has brought back the altered levels of biochemical markers to the near normal levels in the dose dependent manner.